Analysis of Melodic Intonation Therapy (MIT) on Speech Ability in Stroke Patients with Aphasia at Srondol Health Center - Metasari, Sherly; Elisa, Elisa (Journal of Health Science and Medical Therapy, 2024)
The Irreversible brain disorders that cause sequelae in the form of motor aphasia or speech disorders which are mostly clinical manifestations in post-stroke patients cause inability to move, speech problems, perspective, because there are problems with brain function. Melodic Intonation Therapy (MIT) is the development of music as a therapeutic medium to improve language skills that use musical elements (intonation and beats) as therapy to improve language skills for people with aphasia. The purpose of this study is to analyze Melodic Intonation Therapy (MIT) on Speech Ability in Stroke Patients With Aphasia with the research stage based on field research in the Srondol community who experienced Stroke with speech difficulties/Aphasia. This research method uses an experimental quasy with a pre-post test with control group design with a sample of 30 respondents with the results of speech development of aphasia patients, international publications, and guidelines for the management of Melodic Intonation Therapy (MIT) in Stroke Patients with Aphasia. Based on the results of the study, it was found that patients who experienced stroke of the families of stroke patients supported him because family support was very important to maintain and maximize physical and cognitive recovery.